Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To show that the functions [tex]\( f_1(x) = e^x \)[/tex] and [tex]\( f_2(x) = x e^{-x} - e^{-x} \)[/tex] are orthogonal on the interval [tex]\([0, 2]\)[/tex], we need to compute the inner product of these two functions over the given interval and show that this inner product is zero.
The inner product of two functions [tex]\( f_1(x) \)[/tex] and [tex]\( f_2(x) \)[/tex] over the interval [tex]\([a, b]\)[/tex] is defined as:
[tex]\[ \langle f_1, f_2 \rangle = \int_a^b f_1(x) f_2(x) \, dx \][/tex]
In this case, we need to compute:
[tex]\[ \langle f_1, f_2 \rangle = \int_0^2 e^x \left( x e^{-x} - e^{-x} \right) \, dx \][/tex]
Let's simplify the integrand first:
[tex]\[ e^x \left( x e^{-x} - e^{-x} \right) = e^x x e^{-x} - e^x e^{-x} \][/tex]
Then:
[tex]\[ e^x x e^{-x} = x \][/tex]
and
[tex]\[ e^x e^{-x} = 1 \][/tex]
Thus, the integrand becomes:
[tex]\[ x - 1 \][/tex]
Now, the integral to compute is:
[tex]\[ \int_0^2 (x - 1) \, dx \][/tex]
We can split this integral into two simpler integrals:
[tex]\[ \int_0^2 (x - 1) \, dx = \int_0^2 x \, dx - \int_0^2 1 \, dx \][/tex]
First, compute [tex]\(\int_0^2 x \, dx\)[/tex]:
[tex]\[ \int_0^2 x \, dx = \left[ \frac{x^2}{2} \right]_0^2 = \frac{2^2}{2} - \frac{0^2}{2} = \frac{4}{2} = 2 \][/tex]
Next, compute [tex]\(\int_0^2 1 \, dx\)[/tex]:
[tex]\[ \int_0^2 1 \, dx = \left[ x \right]_0^2 = 2 - 0 = 2 \][/tex]
Putting it all together:
[tex]\[ \int_0^2 (x - 1) \, dx = 2 - 2 = 0 \][/tex]
Since the inner product [tex]\(\langle f_1, f_2 \rangle\)[/tex] is zero, this shows that the functions [tex]\( f_1(x) = e^x \)[/tex] and [tex]\( f_2(x) = x e^{-x} - e^{-x} \)[/tex] are indeed orthogonal on the interval [tex]\([0, 2]\)[/tex].
The inner product of two functions [tex]\( f_1(x) \)[/tex] and [tex]\( f_2(x) \)[/tex] over the interval [tex]\([a, b]\)[/tex] is defined as:
[tex]\[ \langle f_1, f_2 \rangle = \int_a^b f_1(x) f_2(x) \, dx \][/tex]
In this case, we need to compute:
[tex]\[ \langle f_1, f_2 \rangle = \int_0^2 e^x \left( x e^{-x} - e^{-x} \right) \, dx \][/tex]
Let's simplify the integrand first:
[tex]\[ e^x \left( x e^{-x} - e^{-x} \right) = e^x x e^{-x} - e^x e^{-x} \][/tex]
Then:
[tex]\[ e^x x e^{-x} = x \][/tex]
and
[tex]\[ e^x e^{-x} = 1 \][/tex]
Thus, the integrand becomes:
[tex]\[ x - 1 \][/tex]
Now, the integral to compute is:
[tex]\[ \int_0^2 (x - 1) \, dx \][/tex]
We can split this integral into two simpler integrals:
[tex]\[ \int_0^2 (x - 1) \, dx = \int_0^2 x \, dx - \int_0^2 1 \, dx \][/tex]
First, compute [tex]\(\int_0^2 x \, dx\)[/tex]:
[tex]\[ \int_0^2 x \, dx = \left[ \frac{x^2}{2} \right]_0^2 = \frac{2^2}{2} - \frac{0^2}{2} = \frac{4}{2} = 2 \][/tex]
Next, compute [tex]\(\int_0^2 1 \, dx\)[/tex]:
[tex]\[ \int_0^2 1 \, dx = \left[ x \right]_0^2 = 2 - 0 = 2 \][/tex]
Putting it all together:
[tex]\[ \int_0^2 (x - 1) \, dx = 2 - 2 = 0 \][/tex]
Since the inner product [tex]\(\langle f_1, f_2 \rangle\)[/tex] is zero, this shows that the functions [tex]\( f_1(x) = e^x \)[/tex] and [tex]\( f_2(x) = x e^{-x} - e^{-x} \)[/tex] are indeed orthogonal on the interval [tex]\([0, 2]\)[/tex].
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.